TOURMALINITE VEINS AND BRECCIAS FROM THE SYMVOLON-KAVALA PLUTON, NORTHERN GREECE: PETROGENETIC PRELIMINARY RESULTS - Xydous, S.; Magganas, A.; Pomonis, P.; Kokkinakis, A. (Bulletin of the Geological Society of Greece, 2016)
A previously undescribed tourmalinite rock consisting of tourmaline-rich veins and breccias occurs within the Lower Miocene Symvolon-Kavala granodiorite pluton, which intrudes the Lower Tectonic Unit of the Rhodope Metamorphic Province. Tourmaline, usually with crypto- to micro-crystalline grain size, is abundant within the matrix of breccias, also forming along with quartz and host rock clasts massive veins and injections in the fractures of the pluton. Field relations indicate that the tourmaline veins and breccias most likely formed in a brittle deformation regime, overprinting the previously developed foliation of the pluton. In addition, mineralogical and textural observations indicate that the precipitation of tourmaline was a result of cooling of B-rich hydrothermal fluids, implying for a possible magmatic-hydrothermal origin for the studied tourmalinite.